PENANAMAN NILAI KESOPANAN, KEJUJURAN DAN TANGGUNG JAWAB MENGGUNAKAN MODEL TADZKIRAHDISEKOLAH DASAR KOTA PONTIANAK - Ariska, Syf.Fatimah; Rosnita, Marzuki; Rosnita, Rosnita (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of the study is describe the model of planting as well as obstacles in cultivating the value of politeness, honesty and responsibility using the model Tadzkirah. This research used qualitative approach with descriptive research type. Research subjects are SD Islam Terpadu Al Mumtaz dan SD Islam Al-Azhar 21 Pontianak. The data source in this research is 2 class teachers and 55 students of class III. Collection techniques used are: observation, interview and documentation. Data analysis is collecting data, reducing data, displaying data and drawing conclusions. Triangulation used source triangulation and method triangulation. The results show that the cultivation of courtesy, honesty, and responsibility values used Tadzkirah model by give exemplary to the learners in all respects, guidance of behaving morally, motivating, getting to say hello and telling the truth, repeating prayers and good habits such as proper prayer time, organizing a sense of patience, and to touch the hearts of learners by providing genuine affection. Obstacles in the value of parental support to participate in habituating the sense of responsibility of learners need to be improved, given that most families of learners are upper economic. The conclusion of this research is that the cultivation of courtesy, honesty, and responsibility values in both schools is well-run and directed.Â Key words: decency, honesty, responsibility, Tadzkirah model.